Inclusive Capitalism in Developing Countries: A case study of Fabindia Overseas Private Limited - Dutt, Devyani (2013)
The inclusive capitalism discourse proposes a case of social good from corporate affairs by engaging with the bottom of the pyramid, that is, the four billion people in the world, living below the poverty line. The discourse relates to market based entrepreneurial activity by including the poor as consumers and producers. Critics of the discourse suggest that viewing the poor as consumers does not increase their income and therefore, does not alleviate poverty. They recommend the poor be viewed as producers in inclusive business models. Viewing the poor as producers, the Henry Jackson Initiative for Inclusive Capitalism (2012) identifies three areas in which corporations, have made positive progress, education for employment, support for small and medium sized enterprises, and improvement of corporate management and governance for the long term. They are referred to as the three pathways to inclusive capitalism. However, evidence of these pathways is limited to developed countries. This paper aims to understand how inclusive capitalism is practiced, and the dual objective of profit and welfare met in developing countries, by viewing positive progress in relation to the three pathways in the developing region. This is done through the case study of an Indian company, Fabindia Overseas Private Limited. Conclusion is presented based on the findings of the case study and recommendations for future research given.